Persepsi Masyarakat Non Muslim Terhadap Minat Menjadi Nasabah Bank Syariah - Nur Rifai; Taufiq Wijaya; Supriyanto Supriyanto (Journal of Finance and Islamic Banking, 2019)
This study aims to determine whether cognitive, affective, and conative perception variables influence the interest of becoming customers of Islamic banks in Surakarta. The research employs quantitative methods, with a sample size of 100 respondents determined using the Slovin formula from a non-Muslim population of 122,130 inhabitants in Surakarta. Data analysis utilizes Multiple Linear Regression Analysis. The findings indicate that, based on the statistical tests, the combined influence of cognitive, affective, and conative perception variables (simultaneously-Test F) positively affects the interest in becoming customers of Islamic banks. The t-test reveals that cognitive perception (X1), affective perception (X2), and conative perception (X3) individually have a positive influence on the interest in becoming customers of Islamic banks (Y), each with a significant level. The regression equation demonstrates that cognitive perception, affective perception, and conative perception variables collectively impact the interest in becoming customers of Islamic banks. Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. The most dominant variable among them is the conative perception variable.